2016
DOI: 10.1371/journal.pbio.1002347
|View full text |Cite
|
Sign up to set email alerts
|

FIH Regulates Cellular Metabolism through Hydroxylation of the Deubiquitinase OTUB1

Abstract: The asparagine hydroxylase, factor inhibiting HIF (FIH), confers oxygen-dependence upon the hypoxia-inducible factor (HIF), a master regulator of the cellular adaptive response to hypoxia. Studies investigating whether asparagine hydroxylation is a general regulatory oxygen-dependent modification have identified multiple non-HIF targets for FIH. However, the functional consequences of this outside of the HIF pathway remain unclear. Here, we demonstrate that the deubiquitinase ovarian tumor domain containing ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 59 publications
3
106
0
Order By: Relevance
“…Another study identified FIH as a second, oxygen-dependent hydroxylase that targets HIF (77,78). Subsequent studies demonstrated that while HIF is clearly the major pathway regulated by hydroxylation, signaling components of other pathways such as NF-κB are also subject to enzymatic hydroxylation, although the functional consequences of hydroxylation for non-HIF targets remains an area under investigation (62)(63)(64)79).…”
Section: Regulation Of Immune Cell Function By Phdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study identified FIH as a second, oxygen-dependent hydroxylase that targets HIF (77,78). Subsequent studies demonstrated that while HIF is clearly the major pathway regulated by hydroxylation, signaling components of other pathways such as NF-κB are also subject to enzymatic hydroxylation, although the functional consequences of hydroxylation for non-HIF targets remains an area under investigation (62)(63)(64)79).…”
Section: Regulation Of Immune Cell Function By Phdsmentioning
confidence: 99%
“…Subsequent studies demonstrated a broader antiinflammatory effect of pharmacological hydroxylase inhibition in diseases such as ischemic acute kidney injury and sepsis, leading to the conclusion that other mechanisms of therapeutic action may also be involved (65,107). Indeed, recent studies have implicated hydroxylase inhibitors in the suppression of cytokine-activated NF-κB-dependent proinflammatory pathways, which may underpin a more general antiinflammatory effect of these drugs (64). Therefore, while hypoxia-sensitive pathways clearly play a complex and multifaceted role in the regulation of immunity and inflammation, the pharmacological activation of these pathways through the application of hydroxylase inhibitors provides a strong, net antiinflammatory effect in multiple models (Figure 3).…”
Section: Preclinical Studies Of Hydroxylase Inhibitorsmentioning
confidence: 99%
“…and IκBα [83] as well as an upstream regulator of the NF-κB pathway, OTU dDeubiquitinase, Ubiquitin Aldehyde Binding 1 (OTUB1), as being hydroxylated by FIH [84,85]. Although these novel FIH targets provide promising links to NF-κB and oxygen sensing, with the exception of OTUB1 [85], mutational analysis has been unsuccessful in identifying any functional significance for these modifications [83,86].…”
Section: Role Of the Oxygen Sensors In The Hypoxia Induction Of Nf-κbmentioning
confidence: 99%
“…Although these novel FIH targets provide promising links to NF-κB and oxygen sensing, with the exception of OTUB1 [85], mutational analysis has been unsuccessful in identifying any functional significance for these modifications [83,86].…”
Section: Role Of the Oxygen Sensors In The Hypoxia Induction Of Nf-κbmentioning
confidence: 99%
See 1 more Smart Citation